Physicochemical Characterisation and Nutritional Evaluation of Oils from Selected Underutilised Oilseeds - Jivini, Za’aku Salvation; Adebisi, Arowora Kayode; Joseph, Ikwebe (Darul Yasin Al Sys, 2024)
The study investigated the physicochemical and nutritional parameters of selected underutilized oilseeds: African oil bean seed, tea seed, African locust bean seed, castor seed, cotton seed and tomato seed. The six oilseed samples were collected from different sources in Nigeria. The seed samples were treated with drying, dehulling and grinding, before they were analysed for the physicochemical and nutritional parameters. The physicochemical parameters determined were: iodine value, peroxide value, free fatty acid, acid value, saponification value, refractive index, specific gravity and pH. The nutritional parameters included: vitamins, minerals, amino acids profile, crude protein and fatty acid profile. The acidity or alkalinity of the oils analysed were measured, the protein contents were analysed using Kjeldahl method, while amino acids determination, fatty acid profile together with water and fat soluble vitamins were determined using Isocratic high performance liquid chromatography (HPLC), minerals were measured using atomic absorption spectrophotometers (AAS). Findings in this study revealed that oils with iodine value less than 100 gI2/100g of oil are considered non-drying oils. Therefore, all the oils in this study are considered to be non-drying oils because their iodine values were less than 100g. Therefore, non-drying oils are not suitable for ink and paint production due to their non-drying characteristics. All the oils analysed in this study were considered fresh because their perioxide values are less than 10 mEq/kg. Fatty acids profile had significance diferences in all the columns. The findings in this study revealed the physicochemical and the nutritional levels of oils from the samples analysed which showed that they all have appreciable nutrient levels which are good for human consumption. The level of protein and essential amino acids are generally higher in Tea seeds oil than other samples analysed. It was further revealed that tea seed oil had highest amount of essential amino acids for lysine, methionine, leucine, tryptophan, threonine and arginine. However African oil bean seed had the highest amount of vitamins A, B2, C, and K and also had the highest level of sodium and potassium.